If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + -1m = -41 Solving -4 + -1m = -41 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1m = -41 + 4 Combine like terms: -4 + 4 = 0 0 + -1m = -41 + 4 -1m = -41 + 4 Combine like terms: -41 + 4 = -37 -1m = -37 Divide each side by '-1'. m = 37 Simplifying m = 37
| 11x-7+3x-1+50=180 | | 22x-7-12x+2=20x-7-10x+17 | | -14-(-5)= | | 1-m+7-6+10m= | | 4m=-17 | | -81-9x=139+x | | 2x-3y+21=0 | | 5x+14=-17 | | -8x+5=28 | | X=100(.2x) | | 11j+4= | | -11(y+3)+5(3y-6)=3(y-3)+13 | | 11x+4-5x=21+7x-3 | | A(x)=x+6x+13 | | 3+21x+14x+12+40=180 | | -2(x-3)=-4x+20 | | X=100+(.2*x) | | lnx+4=1 | | 12x+6-(3x-5)=79 | | -6x=798 | | 32-17+2z=13 | | 8=-1+x | | 3x+11=4X-21 | | 4x+x-5=20 | | 2(x+1)1-4=12 | | 100=x(.02) | | k+-263.48=-381.09 | | 3y-15-8x-16=-2y-22 | | 5b+10=70 | | 7+9p=-110 | | -6x+4=10+8x | | 11x^2=13x+0 |